Stability of Spinning Missiles Guided by Trajectory Tracking Guidance Law - Zhou, Zhiming; Liu, Zhen (Chinese Control and Decision Conference, 2022)
Trajectory tracking guidance is employed widely by low cost missiles for the characteristic of easy to implement. However, for spinning missile, the guidance loop may result in dynamic unstable in the form of a divergent coning motion. Due to the cross-coupling effects between the pitch and yaw channel caused by spinning and the phase lag caused by the actuator, the stability criterions of the trajectory tracking guidance applied to the non-spinning missiles are no longer suitable for spinning missiles. Addressing this issue, a new model based on the state space function has been established in this paper, and the stability criterions for the acceleration autopilot and the tracking guidance loop have been derived. Simulation results illustrate the effectiveness of the stability criterions. It reveals that the trajectory tracking guidance stable region of the coefficients for a spinning missile will shrink a lot compared with the non-spinning missile, if there is no autopilot acting on the control loop, but it will vary little if there is a stable acceleration autopilot with the phase lag compensated acting on the the spinning missile. With increasing of the phase lag, the stable region of the guidance coefficients for the spinning missile becomes smaller.